La integración Corío – Acre: enlace entre militares y civiles sobre los temas de seguridad y defensa de Brasil y Perú - Mendes da Costa, Leandro (2022)
The National Security and Defense Policies of Peru and Brazil are structured documents based on the main objectives considered for the maintenance of the sovereignty of these countries. Due to their geographical position, neighbors in South America, they have the Amazon jungle in common, which is considered a world strategic area, due to the natural resources available. In addition to these characteristics mentioned, we must consider the Latin American culture, even though the Spanish spoken in Peru is different from the Portuguese of Brazil, we have similarities in cultural habits, which makes the coincidence of political and social problems curious. Security and defense issues are rarely explored by the Powers of the State and by society, but the defense policies of both countries describe the need for the involvement of the entire nation to promote national development and, consequently, sustain the sovereignty. Therefore, the main idea of ​​this article is to present the relationship of an integration initiative between Brazil and Peru, through the Corío - Acre axis, with security and defense policies, motivating society to be interested in the defense issue.